Destierro y Encuentro. Aproximaciones al exilio latinoamericano en México 1954-1980 - Mónica Palma Mora (Les Cahiers ALHIM)
During the second half of the XX° century military regimes took over the political structures of many Latin American countries sending into exile thousands of persons. Mexico was one of the many countries that received them. This paper analyses from a general perspective some of the characteristics of the Latin American exile, their integration as well as their participation in the host society and how they have contributed to a better understanding of the specific problems related to migration and exile during the period under consideration.